Women in Online Media News: Critical Discourse Analysis of the Sara Mills Model - Agung, Giovanni Battista; Suroso (Formosa Journal of Sustainable Research, 2023)
This research describes the image of women, subject-object position, and writer-reader position in the Kompas.com, Detik.com, and Republika.co.id news about student bullying at UIN Jambi. Data was collected using reading and note-taking techniques. Data were analyzed using Sara Mills' AWK theory model. The result is that Kompas.com portrays women negatively. Women and the campus as subjects. Women become objects. Writer as subject. The reader is positioned from the perspective of the victim and the campus. Detik.com has a negative image. The campus is the subject and women are the object. The author as subject and reader is placed in the perspective of the campus. Meanwhile, Republika.coid portrays women positively. The subjects are played by women and netizens. Women become objects. The author as subject and reader is placed in a woman's perspective. Therefore, it is hoped that the results of this research will be able to make readers critical of the news